A James Joyce Chronology - Norburn, R. author. aut Link
XIV, 231 p.
Keywords: The Author Chronologies Series aims to provide a means whereby the precise chronological facts of an author's life and career can be seen at a glance. This chronology provides a synopsis of Joyce's first years in Dublin and, from 1900, a more detailed account of his life there and attempts to become established as a writer when living mainly in Trieste and Zurich; and finally (when he became world-famous) Paris, concluding with his death in 1941.